La escena del «Brindis con el Sol» en los queros o vasos de madera andinos de época colonial - Ramos Gómez, Luis (Revista Española de Antropología Americana, 2008)
The scene that traditionally has been denominated “Toast with the Sun” is one of the decorative subjects of the Andean wood vessels of colonial time. In this work, we analyze the studies on the variants of the scene and raised a new hypothesis. For us, the initial image reproduced an space and a concrete episode of the confrontations between Incas and Collas, while that the later versions adjusted more to the traditional Andean rites for the agricultural production.